2005
DOI: 10.1897/04-125r.1
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal study on the Cd, Se, and Zn uptake by natural coastal phytoplankton assemblages

Abstract: We conducted a seasonal study of the uptake of Cd, Se(IV), and Zn by natural phytoplankton assemblages collected from two locations in Hong Kong coastal waters. Marine phytoplankton in Port Shelter was dominated by diatoms and cyanobacteria, while phytoplankton in Tolo Harbour was dominated by dinoflagellates. The natural phytoplankton assemblages were spiked with macronutrients (N and P) and metals, and the accumulation of these metals was followed for 3 to 5 d in the laboratory. The two coastal systems were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
13
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 36 publications
1
13
1
Order By: Relevance
“…Mesocosm studies have confirmed those findings by adding nutrients to stimulate a bloom under controlled conditions. For example, Riedel and Sanders (2003) found that dissolved Zn was depleted in mesocosm studies with Patuxent River water, and Wang et al (2005) showed that phytoplankton accumulated Zn from Hong Kong coastal waters. The contrasting results in our study could be because (1) sampling started too late to capture a Zn drawdown, (2) Zn was rapidly repartitioned from the particulate phase, (3) organic complexation limited Zn bioavailability, or (4) a combination of these factors.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Mesocosm studies have confirmed those findings by adding nutrients to stimulate a bloom under controlled conditions. For example, Riedel and Sanders (2003) found that dissolved Zn was depleted in mesocosm studies with Patuxent River water, and Wang et al (2005) showed that phytoplankton accumulated Zn from Hong Kong coastal waters. The contrasting results in our study could be because (1) sampling started too late to capture a Zn drawdown, (2) Zn was rapidly repartitioned from the particulate phase, (3) organic complexation limited Zn bioavailability, or (4) a combination of these factors.…”
Section: Discussionmentioning
confidence: 99%
“…Along with nutrients, trace metals have also been depleted by blooms in South Bay , the Scheldt estuary (Zwolsman and van Eck 1999), coastal waters (Schoemann et al 1998;Ingri et al 2004), and laboratory mesocosm studies (Beck et al 2002;Riedel and Sanders 2003;Wang et al 2005). In South Bay, the 1994 spring bloom depleted dissolved Cd, Ni, and Zn (but not Cu) from the water .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Tolerance and removal of toxic metal ions have been studied in bacteria [14][15][16][17][18][19][20], cyanobacteria [21,22], algae [23][24][25][26] and fungi [27][28][29]. Eccles, [30] has opined that the microbiological detoxification of polluted water is economical, safe and sustainable.…”
Section: Introductionmentioning
confidence: 99%
“…Chemical contaminants can affect negatively the metabolic activities of vegetative cells of various phytoplankton species, inhibiting their growth and survival at determined concentrations (e.g., Rai et al, 1998;Mosulén et al, 2003;Wang et al, 2005;Miao and Wang, 2006;Herzi et al, 2013). Until now, most of the ecotoxicological studies conducted on dinoflagellates investigated the effects of contaminants only on vegetative cells.…”
Section: Introductionmentioning
confidence: 99%